A case of pulseless electrical activity due to takotsubo syndrome following radiofrequency catheter ablation for atrial fibrillation. Issue 6 (December 2020) - Oka, Takafumi; Tanaka, Kota; Inoue, Hiroyuki; Ninomiya, Yuichi; Tanaka, Koji; Hirao, Yuko; Tanaka, Nobuaki; Okada, Masato; Takayasu, Kohtaro; Kitagaki, Ryo; Koyama, Yasushi; Okamura, Atsunori; et al.
Abstract: A 51-year-old man with normal left ventricular ejection fraction (LVEF) underwent radiofrequency catheter ablation (RFCA) for long-standing persistent atrial fibrillation (AF). After isolating the pulmonary veins (PV), we attempted to ablate multiple non-PV AF triggers evoked by isoproterenol and performed repetitive intracardiac electrical cardioversion under considerable dose of barbiturate. Finally, administration of pilsicainide was required to maintain sinus rhythm. Sixty minutes after the procedure, initiation of development of rapid ST-segment elevation was observed on the continuous electrocardiogram monitor and the patient complained of general fatigue. There was occurrence of complete atrioventricular block and he immediately fell into pulseless electrical activity (PEA). Cardiopulmonary resuscitation was initiated and a percutaneous cardiopulmonary system (PCPS) was provided. Echocardiogram showed severe biventricular systolic dysfunction. Although ST-segment change sustained, emergent coronary angiography was normal. Left ventriculogram showed apical to mid ventricular akinesia and preserved basal contractibility, which was typical of takotsubo syndrome (TS). Fortunately, he recovered completely; the PCPS was weaned on day 5, and the LVEF normalized within 2 weeks without any neurological disorders. This is the first case report of PEA due to TS following AF ablation. TS due to stressors of RFCA procedure should be recognized as a possible life-threatening complication. <Learning objective: Invasive medical procedures can trigger takotsubo syndrome (TS), which is occasionally fatal. TS due to radiofrequency catheter ablation (RFCA) procedure should be recognized as a life-threatening complication following RFCA. Pulseless electrical activity due to TS after RFCA procedures requires precise clinical evaluation, close monitoring, and appropriate management.>